2020
DOI: 10.1152/jn.00562.2020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reproducibility of electroencephalography-based corticokinematic coherence

Abstract: Corticokinematic coherence (CKC) is the phase coupling between limb kinematics and cortical neurophysiological signals reflecting cortical processing of proprioceptive afference, and is reproducible when estimated with magnetoencephalography (MEG). However, feasibility and reproducibility of CKC based on electroencephalography (EEG) is still unclear and is the primary object of the present report. Thirteen healthy right-handed volunteers (7 females, 21.7 ± 4.3 years) participated two separate EEG sessions 12.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 36 publications
8
23
0
Order By: Relevance
“…The result was replicated in the source-level analysis which showed ~28% stronger CKC for the simultaneous stimulation. Our result extends previous studies that have stimulated the proprioceptors related to the index finger (Bourguignon et al, 2016;Piitulainen et al, 2015Piitulainen et al, , 2018bPiitulainen et al, , 2020. We showed that the coherent proprioceptive afference from all induced fingers sum up to the SM1 cortex proprioceptive processing.…”
Section: Stronger Ckc To Simultaneous Than Separate-finger Stimulatiosupporting
confidence: 91%
See 3 more Smart Citations
“…The result was replicated in the source-level analysis which showed ~28% stronger CKC for the simultaneous stimulation. Our result extends previous studies that have stimulated the proprioceptors related to the index finger (Bourguignon et al, 2016;Piitulainen et al, 2015Piitulainen et al, , 2018bPiitulainen et al, , 2020. We showed that the coherent proprioceptive afference from all induced fingers sum up to the SM1 cortex proprioceptive processing.…”
Section: Stronger Ckc To Simultaneous Than Separate-finger Stimulatiosupporting
confidence: 91%
“…As expected, the peak CKC locations were concentrated on the Rolandic SM1 cortex (within ~8 mm) replicating previous results obtained by proprioceptive stimulation of the index finger (Bourguignon et al, 2016;Piitulainen et al, 2020Piitulainen et al, , 2018bPiitulainen et al, , 2015. However, the exact spatial coordinates for CKC source have been reported previously only for passive index finger movements elicited by an experimenter (Piitulainen et al, 2013b), not by precise stimulator.…”
Section: Ckc Source Locations Were Concentrated On the Hand Region Ofsupporting
confidence: 89%
See 2 more Smart Citations
“…Cortical processing of proprioceptive afference (i.e., from the “movement sensors,” for review see (Proske & Gandevia, 2012) to the primary sensorimotor (SM1) cortex can be examined using precise computer controlled movement actuators, that is, proprioceptive stimulators, in magnetoencephalography (MEG; Alary et al., 2002; Lange et al., 2001; Piitulainen et al., 2015), electroencephalography (EEG; Desmedt & Ozaki, 1991; Mima et al., 1996; Piitulainen et al., 2020) or functional magnetic resonance imaging (MRI; Nurmi et al., 2018; Weiller et al., 1996). Corticokinematic coherence (CKC) can be used to quantify the coupling between oscillatory cortical activity measured with electrophysiological recordings (MEG or EEG) and limb kinematics ( e.g ., acceleration, force, etc.…”
Section: Introductionmentioning
confidence: 99%